The Role of the Life Skills Program in Increasing the Productivity of Golden Dragon Fruit Entrepreneurs - Hidayah, Martin; Riyanto , Yatim; Widodo , Widodo (Universitas Negeri Semarang, 2024)
Education focuses more on subjects rather than life skills which play an important role in facing the complexity of the world of work. This research uses a descriptive qualitative research approach. The aim of the research is to explore the impact of the life skills education program on the productivity of golden dragon fruit entrepreneurs at Anggrek Bulan CLC in Banyuwangi. Through this program, it is hoped that entrepreneurs will be able to optimize their businesses, increase crop yields, and open up opportunities for business growth in a competitive market. This research was conducted at Anggrek Bulan CLC in Banyuwangi. The subjects in this research were managers and students of the golden dragon entrepreneurship program at Anggrek Bulan CLC in Banyuwangi. Data collection techniques use in-depth interviews, participant observation and documentation. The data validity technique used in this research is the triangulation technique. Next, the data analysis technique uses Miles and Hubermen analysis. The results of the research are 1) Increased Knowledge and Skills, the life skills education program provides opportunities for participants to gain the knowledge and skills needed to manage the Golden dragon fruit business more effectively. These include managerial, financial, marketing, and agricultural technical skills. 2) Relevance to Market Needs, participants are given insight into marketing strategies, product innovation and the latest technology that helps them remain competitive in an ever-growing market. 3) Involvement of External Parties, involving industry experts, successful entrepreneurs, and research institutions has enriched the program with additional experience and knowledge